2017
DOI: 10.1186/s12942-017-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of excess mortality during prolonged dust events in a high-density city: a time-stratified spatial regression approach

Abstract: BackgroundDust events have long been recognized to be associated with a higher mortality risk. However, no study has investigated how prolonged dust events affect the spatial variability of mortality across districts in a downwind city.MethodsIn this study, we applied a spatial regression approach to estimate the district-level mortality during two extreme dust events in Hong Kong. We compared spatial and non-spatial models to evaluate the ability of each regression to estimate mortality. We also compared prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
1
13
0
1
Order By: Relevance
“…To identify spatial autocorrelation in the SPAR values, Moran’s I statistics were calculated for the accessibility values from three modes of travel. Due to the presence of spatial autocorrelation, spatial regression [46,47,48] was performed in R to account for spatial dependency, providing more accurate regression results.…”
Section: Methodsmentioning
confidence: 99%
“…To identify spatial autocorrelation in the SPAR values, Moran’s I statistics were calculated for the accessibility values from three modes of travel. Due to the presence of spatial autocorrelation, spatial regression [46,47,48] was performed in R to account for spatial dependency, providing more accurate regression results.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term exposure to high PM10 concentrations can increase the risk of mortality through respiratory and cardiovascular diseases (e.g., Kotsyfakis et al, 2019). Multiple reports suggested that an increase in the nonaccidental mortality by up to more than 10% due to prolonged (≥3 days) high PM10 episodes (Kim et al, 2018a(Kim et al, , 2018bPizzo & Clerico, 2012;Wang et al, 2018;Wong et al, 2017;Zhang et al, 2017;Zhou et al, 2015), much higher than the mortality rate caused by shorter duration events (<3 days). (ii) Severe widespread prolonged dust events are triggered and maintained by persistent synoptic circulations (e.g., Beegum et al, 2018;Dumka et al, 2019;Hamidi et al, 2017Hamidi et al, , 2014Houssos et al, 2015;Knippertz & Fink, 2006;Knippertz & Stuut, 2014;Shao et al, 2010;Solomos et al, 2017).…”
Section: Identification Of Extreme Dust Eventsmentioning
confidence: 99%
“…Data-driven approaches to map local areas with higher vulnerability are commonly used for preventive healthcare and emergency planning [ 23 , 24 , 25 , 26 ]. These vulnerability maps can be used for identifying significant hotspots of different health risks, and were previously applied to government-based protocols for the purpose of: (1) targeting areas with higher general health risk of vulnerable population [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]; (2) locating higher risk areas during specific events such as violent trauma, heat waves and extreme pollution events [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]; and (3) predicting spatial variability of non-communicable diseases such as cancer [ 46 , 47 , 48 ]. However, data-driven methods to predict the spatial variability of geriatric depression have rarely been investigated, leading to insufficient preventive measures to such an increasingly common disease among the senior population.…”
Section: Introductionmentioning
confidence: 99%